Pijat bayi dan kenaikan berat badan bayi usia 0-4 bulan - Agnes Rehulina; Hesty Widyasih; Sabar Santosa (Poltekkes Kemenkes Yogyakarta, 2014)
In infancy , the weight can be used to look at the rate of physical growth and nutritional status of infants . Infant massage is analternative to achieve optimal growth and development .Research with the experimental study and design ofpre - post test designwith control group was aimed to know the effect of infant massage on weight gain of infants aged 0-4 months at Panii NugrohoHospital Pakem. The study was conducted on 29March to 17April 2012.Samples of this study are infants 0-4months thatmeet thecriteria: healthy babies , cared for both parents,exclusively breast-fed and did not have birth defects .Group treatment control groupamounted to 15 babies each . Infantmassage is done 2 times in 1 week in a 3 -week period with a 15minute longmassage . Beforeand after the massage baby weighed and recorded in the observation sheet . Test hypothesis with 95%confidence level and errorlevel of 5%with the application of R Commander with Paired Sample T - Test and Independent sample t - test. The results showedPaired Sample T - Test in the treatment group known p -value of 4.075 e- 05 with an average of 630 grams weight gain . In controlgroup showed p-vaiue 0.08297with an average of 83 gramsweight gain. Independent samplet- test obtainedp -value of 0.000161.So there isan effect of infantmassage onweight gain of infants aged 0-4months .